IMPLEMENTASI RENCANA KERJA PEMERINTAH DESA (RKPDES) DALAM BIDANG PEMBANGUNAN DESA TANAH MERAH KECAMATAN TANAH MERAH KABUPATEN INDRAGIRI HILIR - Abdul Halim; Dadang Mashur (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research is motivated by Infrastructure Development of Tanah Merah Village, Tanah Merah Sub-district, Indragiri Hilir Regency that has not been realized well in accordance with the Tanah Merah Village Development Program Activity Plan as stated in RKPDes Desa Tanah Merah document. The purpose of this research is to find out how is the Implementation of Village Government Work Plan (RKPDes) in the Village Development Sector of Tanah Merah based on Indragiri Hilir Regent Regulation No. 27 of 2016 about Regional Development Plans Indragiri Hilir Regency in 2016 Year and what factors that affect the Implementation of Government Work Plan (RKP) in 2016 Year at the field of development of the village of Tanah Merah.Based on the formulation above of the research problems, to answer the purpose of research, the authors use the theory Tachjan (2006: 8). According to him, there are three things that must be fulfilled in the absolute implementation of: First, the Implementing Elements, Second, Programs conducted, Third, Target Group.While the method used in this research is descriptive qualitative, in the form of primary and secondary data. Data collection techniques such as observation and interview. Determination method of research informant used is triangulation technique. Research location in Tanah Merah Village and Tanah Merah Village Office Tanah Merah Sub-district Indragiri Hilir Regency.The result of the research shows that the Implementation of Village Government Work Plan (RKPDes) in the Village Development Sector of Tanah Merah Tanah Merah Sub-district of Indragiri Hilir Regency conducted by Tanah Merah Village with a description of who becomes the implementing element of the village development program and how it is implemented. In the implementation of the system has not been realized optimally with influencing factors such as communication factors and geographical factors.Keywords: Implementation of the Policy, RKP